Student Retention/Attrition. - Polka, Joseph (1998)
Keywords: dept.soc; faculty_collection; sabbatical_report

The Social Charcteristics of Recent Graduated of Irish Universities Who Emigrate for Overseas Employment. - Ryan, Michael (1991)
Keywords: dept.soc; faculty_collection; sabbatical_report

History of American Women's Resistance to War: Anthology of Writings. - McCarthy, Katherine (1990)
Keywords: dept.soc; faculty_collection; sabbatical_report

Social Problems - Doob, Christopher Bates (Harcourt Brace College Publishers, 1995)
[This book] focus[es] on topics [such as:] the corporate state, an emphasis on the impact of the power elite in a capitalist state; the environment, pollution and depletion of resources, with a new sense of urgency created for alleviating if not solving these chronic problems; urban deterioration, the steady decline in the physical and cultural quality of city life, with little successful effort to plan cities with citizens' basic needs and interests in mind; racism, the legacy of our nation's racist past carrying into the present and still impacting heavily on many citizens, most notably the minority poor; sexism, men's traditional domination of women ... youth problems, a variety of major difficulties facing many young people [and] crime, an analysis of some of the most disturbing, damaging types of crime ravaging the modern United States. These subjects are examined in depth, with diverse, primarily recent source material used. -Pref.
Keywords: Social problems; Sociology; dept.soc; faculty_collection

New Spirituality, Self, and Belonging: How New Agers and Neo-Pagans Talk About Themselves - Bloch, Jon P. (Religion in the age of transformation, 1998)
Keywords: Case studies; Neopagans; Case studies; New Age movement; Interviews; Interviews; Neopagans; New Age persons; Psychology; Social aspects; Neopaganism; Social aspects; New Age persons; dept.soc; faculty_collection

Racism: An American Cauldron - Doob, Christopher Bates (HarperCollinsCollege, 1996)
Keywords: Race relations; Racism; United States; United States; dept.soc; faculty_collection

Racism: An American Cauldron - Doob, Christopher Bates (Longman, 1999)
Keywords: Race relations; Racism; United States; United States; dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates (Harcourt Press, 1997)
Keywords: Sociology; dept.soc; faculty_collection

Alternative spirituality and environmentalism - Bloch, JP (Review of Religious Research, 1998)
The relationship between religiosity and environmentalism has previously been examined by studying conservative versus liberal Christian affiliation. This study explores environmentalist attitudes amongst persons whose religiosity does not fit conventional patterns: the so-called “alternative” or “countercultural” spiritual community (e.g, New Age, Neo-Paganism). This network of individuals finds commonalty and solidarity not through organizational ties or a singular theology, but through an overriding ideology that challenges the alleged rigidity and dualistic dogma of mainstream society, and so suggests a new form of social movement. Central to this critique of the mainstream is the notion that the earth is just as sacred as the “heavens,” and so by preserving the earth, one is being “spiritual. “ Excerpts from in-depth interviews with 22 alternative spiritualists feature numerous key environmental/spiritual themes. These excerpts indicate that issues such as religiosity, “liberal” versus “conservative” affiliation, and environmental politics can take on different meanings when explored outside of mainline Christianity.
Keywords: dept.soc

Gauging the strength of evidence prior to plea bargaining: the interpretive procedures of court-appointed defense attorneys - Emmelman, Debra S (Law and Social Inquiry-journal of The American Bar Foundation, 1997)
An important debate among court observers is whether plea bargaining undermines the ideals of justice. This article presents findings that may reconcile some inconsistent research conclusions. It describes how, prior to plea bargaining, one group of court-appointed defense attorneys gauges the strength of evidence through a tacit, taken-for-granted process that emulates trial proceedings: based on their understanding of evidence in the legal community, defenders imagine a courtroom dialogue wherein the prosecution and defense take turns presenting their cases in front of a judge and jury. At issue throughout the dialogue is whether or to what extent information is sufficient, legal, and persuasive enough to convict the defendant. Because the process is part of the defenders' ongoing and unspoken daily routines, it may elude unsuspecting investigators. Ironically, this means not only that some analysts may inappropriately conclude that legal ideals play no role in plea bargaining but also that: others may ingenuously assume that such behavior is more ethical than it actually is.
Keywords: dept.soc

Trial by plea bargain: Case settlement as a product of recursive decisionmaking - Emmelman, DS (Law & Society Review, 1996)
Through presentation of ethnographic research findings on court-appointed defense attorneys, this article examines plea bargaining as a component of a recursive process for deciding whether a case should be settled immediately or proceed further. The decisionmaking process has three types of activities: assessing the offer for a guilty plea, negotiating the terms of a plea bargain, and counseling the defendant and deciding on a course of action. Until a criminal case is actually settled either through a final plea agreement or a jury trial, this decisionmaking process occurs over and over again. Viewed as a component of this recursive process, plea bargaining encompasses multiple episodes of negotiating behavior as well as a wide range of formal litigation proceedings. Perhaps more important, plea bargaining and trial procedures can actually be seen to converge. I conclude that this mode of plea bargaining is not merely an effective method for representing defendants but perhaps equally or more effective than trial. Some important limitations of the findings are also discussed.
Keywords: dept.soc